Svietlova A. Linguocultural studies of communicative silence - Svietlova A. (Philological Treatises, 2020)
The article deals with the aspects and the factors of communicative silence in the process of intercultural communication. Linguistic picture of the world and the role of the language personality of a translator in the process of information overcoding are considered.